2021
DOI: 10.1007/s12062-021-09345-3
|View full text |Cite
|
Sign up to set email alerts
|

How do Older Adults Spend Their Time? Gender Gaps and Educational Gradients in Time Use in East Asian and Western Countries

Abstract: This study is the first to document how older adults in East Asian and Western societies spend their time, across four key dimensions of daily life, by respondent’s gender and education level. To do this, we undertook a pioneering effort and harmonized cross-sectional time-use data from East Asian countries (China, Japan, South Korea, Taiwan) with data from the Multinational Time Use Study (Canada, Denmark, Finland, France, Italy, The Netherlands, Norway, Spain, United Kingdom, United States; to which we refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Normally tobit models are used to handle this condition. However, as argued by Kan et al (2021) and referring to Foster and Kalenkoski (2013) and Stewart (2013), evidence suggests that OLS estimates are similar to those obtained from tobit models and are also unbiased and robust to several critical assumptions about the relationship between the factors of the model and the probability of doing an activity.…”
Section: Methods Of Analysismentioning
confidence: 78%
“…Normally tobit models are used to handle this condition. However, as argued by Kan et al (2021) and referring to Foster and Kalenkoski (2013) and Stewart (2013), evidence suggests that OLS estimates are similar to those obtained from tobit models and are also unbiased and robust to several critical assumptions about the relationship between the factors of the model and the probability of doing an activity.…”
Section: Methods Of Analysismentioning
confidence: 78%
“…Another subset of research categorizes activities based on the level of energy expenditure (c.f., classification of energy costs of daily activities [1]), as reflected in many physical activity questionnaires they developed to assess older adults' intensityspecific duration for behavior (e.g., MOST [33], CHAMPS [114], LASA [125]). Domestic and leisure activities are prevalent in older adults' daily activities [49,55,79,83]. According to the national time use surveys from 14 countries, older adults (aged 60-75) spent around 6 hours on leisure and ≥2.5 hours on domestic work daily [55].…”
Section: Understanding Older Adults' Activitiesmentioning
confidence: 99%
“…Domestic and leisure activities are prevalent in older adults' daily activities [49,55,79,83]. According to the national time use surveys from 14 countries, older adults (aged 60-75) spent around 6 hours on leisure and ≥2.5 hours on domestic work daily [55]. From the interviews with U.S. older adults, Moss and Lawton found that participants spend about 5 hours a day on obligatory personal care & household activities and more than 6 hours a day on discretionary leisure activities [83].…”
Section: Understanding Older Adults' Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all ages, people in China and India devote more time to paid work than people in the MTUS countries and less time to leisure and unpaid work. While most of the empirical literature on time use focuses on high-income countries (a notable exception is Kan et al, 2021), the paper compares countries at different levels of development.…”
Section: Introductionmentioning
confidence: 99%